PRUNE BELLY SYNDROME - Alam, Malik Mahmood (Journal of Ayub Medical College Abbottabad, 2015)
This is a 3 days old baby who presented to women and children Hospital Abbottabad with history of abdominal distension which was present since birth. He was passing stool and feeding well. He was given glycerine suppositories with the assumption that he may be having constipation. It did not make any difference to the abdominal distension and therefore this referral. On examination he did not have any abdominal muscles and viscera was palpable especially his kidneys. Both testes were not palpable. Prune Belly syndrome presents with deficient abdominal muscles, undescended testes and urinary tract malformations.1,2 It is also called Abdominal Muscle deficiency syndrome or Eagle Barrett syndrome.3 Sepsis due to urinary tract infection may be significant cause of morbidity due to dilated urinary tract and pooling of the urine.4,5 There may be dilatation without Obstruction and cardiac and musculoskeletal abnormalities as well. The incidence is 1:40000 births and 95% of the affected are males. Management depends upon the renal complications including antibiotic prophylaxis to prevent Urinary tract infections. Early surgery for the renal tract abnormalities may be performed. Surgery for undescended testes needs to be done as well. Abdominal reconstruction surgery may be advisable in some. Prognosis depends upon renal and pulmonary abnormalities.